2012
DOI: 10.1093/humrep/des173
|View full text |Cite
|
Sign up to set email alerts
|

Higher clusterin immunolabeling and sperm DNA damage levels in hypertensive men compared with controls

Abstract: This pilot study strongly suggests a relationship between hypertension and markers indicative of poor sperm quality. In hypertensive subjects, high levels of clusterin immunolabeling identified a consistent fraction of ejaculated spermatozoa carrying both DNA fragmentation and strong morphological alterations, which was not correlated with age or with sperm cell mortality. The alternative possibility that sperm damage observed is due to adverse effects of anti-hypertensive drugs does not find support in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
3
28
0
2
Order By: Relevance
“…In the current study, it was found that sCLU negatively correlates with sperm morphology, protamine deficiency, and DNA fragmentation since less sCLU was detected in the seminal plasma of infertile patients. Although extensive research has been previously done on the relationship between CMA 3 -positivity, DNA damage, seminal CLU gene expression, and infertility (Zini et al, 2001;Nasr-Esfahani et al, 2004Muciaccia et al, 2012;Zalata et al, 2012), to our knowledge this is the first report on the correlation between sCLU of seminal plasma, sperm parameters, protamine deficiency, and DNA fragmentation in humans.…”
Section: Discussionmentioning
confidence: 93%
“…In the current study, it was found that sCLU negatively correlates with sperm morphology, protamine deficiency, and DNA fragmentation since less sCLU was detected in the seminal plasma of infertile patients. Although extensive research has been previously done on the relationship between CMA 3 -positivity, DNA damage, seminal CLU gene expression, and infertility (Zini et al, 2001;Nasr-Esfahani et al, 2004Muciaccia et al, 2012;Zalata et al, 2012), to our knowledge this is the first report on the correlation between sCLU of seminal plasma, sperm parameters, protamine deficiency, and DNA fragmentation in humans.…”
Section: Discussionmentioning
confidence: 93%
“…Besides these three significant proteins mentioned above, we also studied another protein – clusterin that was reported to be important in the maturation of spermatozoa 656667. It is secreted by the epididymis and seminal vesicle and is found to have a positive relationship with DNA fragmentation and morphological abnormalities of the spermatozoa 68. Higher expression level of clusterin has been reported in infertile patients than in fertile men 69.…”
Section: Discussionmentioning
confidence: 99%
“…Akagashi et al (1997) found an extreme spermatogenic impairment in the form of atrophic seminiferous tubules devoid of spermatids in stroke-prone spontaneously hypertensive rats. Very recently, a study of semen quality in hypertensive men demonstrated an association between hypertension with more fragmented/abnormal sperm DNA and with increased expression of clusterin, an apoptosisassociated protein, which identifies a subset of morphologically altered spermatozoa not necessarily dead (Muciaccia et al, 2012). In that study, (Muciaccia et al, 2012) the link between elevated blood pressure and abnormal morphology/DNA fragmentation was not clarified, but it was hypothesized that hypertension induces, within the testis, a generally altered vascular status characterized by enhanced ROS generation and limited antioxidant defence (Sharma et al, 1999;Brownlee, 2005;Amaral et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a study of semen quality in hypertensive men demonstrated an association between hypertension with more fragmented/abnormal sperm DNA and with increased expression of clusterin, an apoptosisassociated protein, which identifies a subset of morphologically altered spermatozoa not necessarily dead (Muciaccia et al, 2012). In that study, (Muciaccia et al, 2012) the link between elevated blood pressure and abnormal morphology/DNA fragmentation was not clarified, but it was hypothesized that hypertension induces, within the testis, a generally altered vascular status characterized by enhanced ROS generation and limited antioxidant defence (Sharma et al, 1999;Brownlee, 2005;Amaral et al, 2008). Another recently published report (Mbah et al, 2012) indicates that treating normotensive, oligospermic men Table 4 Comparisons between subjects with metabolic syndrome (MetS) and 1 : 3 ratio matched controls (matched for age, body mass index, total testosterone, smoking habit, alcohol consumption, past or present cryptorchidism, leucocytospermia, current positive urine and/or semen cultures with a low-dose angiotensin converting enzyme inhibitor (lisinopril, 2.5 md/daily) ameliorates, in a rigorous placebo-controlled, crossover design, semen parameters, including sperm number, motility and morphology.…”
Section: Discussionmentioning
confidence: 99%